Influence of decompression sickness on vasomotion of isolated rat vessels - Mazur, A.; Lambrechts, K.; Buzzacott, Peter; Wang, Q.; Belhomme, M.; Theron, M.; Mansourati, J.; Guerrero, F. (Georg Thieme Verlag, 2014)
Several studies have demonstrated that endothelial function is impaired following a dive even without decompression sickness. During this study we determined the effect of decompression sickness on endothelium-dependent and independent vasoreactivity. For this purpose twenty-seven male Sprague-Dawley rats were submitted to a simulated dive up to 1 000 kPa absolute pressure and divided into 3 groups: safe diving without decompression sickness or dives provoking mild or severe sickness. A fourth control group remained at atmospheric pressure. Endothelium-dependent and independent vasomotion was assessed ex vivo by measuring isometric tension in rings of abdominal aorta and mesenteric arteries. Dose-response curves were obtained with phenylephrine, acetylcholine and sodium nitroprusside. Acetylcholine-induced relaxation was measured in the presence of L-NAME, indometacin or both of them at once.Contraction was significantly decreased after each protocol compared with the control rats. Additionally, the response in animals from the severe group was significantly different from that of the safe and mild groups. Dose response curves for acetylcholine alone and in the presence of inhibitors remained unchanged. We did not observe differences in endothelium-dependent vasodilation after diving or in the presence of decompression sickness. Contractile response to phenylephrine was progressively impaired with increased decompression stress. These results may indicate smooth muscle injury. © Georg Thieme Verlag KG Stuttgart New York.